Effects of COVID-19 nursing home restrictions on people with dementia involved in a Supportive Care programme - Paccagnella, Omar; Miele, Francesco; Guzzon, Angelica; Neresini, Federico; Rebba, Vincenzo; Rigon, Michela; Boniolo, Giovanni (Frontiers in Health Services, 2024)
BackgroundSupportive Care is a person-centred approach encompassing non-pharmacological interventions targeted towards persons with dementia to contain the effects of their behavioural disorders, improving their quality of life.AimsTo investigate the effects of lockdown restrictions during the first wave of COVID-19 pandemic on behavioural symptoms of patients involved in a Supportive Care programme in an Italian nursing home.MethodsAnalysis is based on Neuropsychiatric Inventory (NPI) scores and related symptoms data collected before (October/November 2019) and after (July 2020) the introduction of COVID-19 restrictions on a non-random sample of 75 patients living in two units of the facility: 38 involved in a Supportive Care programme and 37 receiving standard care (Control). Group performances were compared over time according to univariate statistics and Latent Class Analysis (LCA).ResultsNPI scores and number of reported symptoms in NPI evaluations increased over time among Supportive Care patients with dementia and decreased in the Control group. Differences are statistically significant. LCA resulted in 3-classes and 5-classes specifications in the two time-occasions.DiscussionSupportive Care patients showed a worsening in behavioural and psychological symptoms after the first pandemic wave, as opposed to the elderly not involved in the programme. LCA showed that patients in the two groups differed according to the combinations of NPI symptoms.ConclusionsThe discontinuation of a Supportive Care programme due to COVID-19 restrictions had strong negative effects on nursing home persons with dementia involved in the programme: Supportive Care interventions are important in controlling the psycho-behavioural symptoms associated with dementia.